Absorption behavior for R1234ze(E) and R1233zd(E) in [P66614][Cl] as working fluids in absorption refrigeration systems. (November 2021) - Jiang, Tao; Meng, Xiangzhao; Sun, Yanjun; Jin, Lijun; Wei, Qiming; Wang, Jiang; Wang, Xiaopo; He, Maogang
Abstract: The absorption-cycle technology driven by low-grade thermal energy has attracted significant attention. Hydrofluoroolefins refrigerant and ionic-liquid absorbent have been currently proposed as the promising candidates to traditional NH3 /H2 O and H2 O/LiBr working pairs. The properties of refrigerant/absorbent pairs have a vital impact on the efficiency of an absorption-refrigeration cycle, especially the solubility of the gaseous refrigerant in an absorbent. In this work, solubilities were measured for two new working pairs (R1234ze(E)/[P66614 ][Cl] and R1233zd(E)/[P66614 ][Cl]) by an isochoric saturation method at the temperature range from 283.15 to 343.15 K. Solubilities increase with the increase of pressure and decrease with increase of temperature. To assess solubility model of refrigerant/IL pairs, the Krichevsky-Ilinskays (KI) equation and Nonrandom Two-Liquid (NRTL) model were used to correlate the new data. From the results, we found that the NRTL model could provide smaller deviations than KI equation. In contrast with the existing IL, the [P66614 ][Cl] has the highest solubility. Furthermore, the enthalpy, entropy, and Gibbs energy of dissolution were estimated.